ANALISIS INTERNALISASI SIKAP PROFIL LULUSAN MAHASISWA PGMI BERBASIS LEVEL AFEKTIF - Muthia Afifah; Nida Murwandini; Dita Ayu Nur Afrilia; Alina Halda Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Affective domain self-assessment is frequently challenged by subjectivity and overestimation biases, often leading to excessively positive outcomes among students. This study aims to evaluate the affective attitude profile of Islamic elementary school teacher candidates based on Krathwohl’s affective taxonomy levels, focusing on the achievement of graduate profile dimensions. A descriptive quantitative method was employed through a survey involving 32 fourth-semester students of the Primary School Teacher Education (PGMI) program at UIN Syarif Hidayatullah Jakarta. Data were collected using a self-assessment instrument consisting of a 40-item questionnaire that measures eight graduate profile dimensions across five distinct affective levels. The data analysis revealed that the collective attitude quality of the students falls into an exceptionally high category. Specifically, 29 students (90.6%) achieved the "Highly Developed" status, signifying they have reached the characterizing level where core character values are fully internalized as spontaneous daily habits. Meanwhile, the remaining 3 students (9.4%) achieved the "Well Developed" status at the organizing level, demonstrating a stable internal value system that is still undergoing consolidation. These findings indicate a strong moral commitment among respondents, while simultaneously providing critical implications for the necessity of developing more objective and comprehensive affective assessment methods to validate self-reporting outcomes in higher education.